(untitled) (Mayéutica Revista Científica de Humanidades y Artes, 2025)
The purpose of the article is to elucidate the relevance of the significant networks of language and discourse through the cultural and social semiotics of Lotman (1996), Verón (1987), Saussure (2008) and Pierce (1931). In this sense, it makes a historical preamble on the origin of Lotman’s cultural semiotics (1996), taking into account the study of semiospheres, semantics and semiotics in discursive narrative, properly. Likewise, the importance of sociosymbolic referents and the strength of the symbol in postmodern society, is considered as well as narrative identity as a representative element within language Paul Ricoeur (1990), since the subject through the word is an enunciator/attributor of its own realitycontext. Likewise, the semiotic turn of Paolo Fabbri (2000), and the semiosis and social imaginary according to Hernández (2023), are deepened through imagination (the myth), narration (refoundation) and the aesthetic moment. The narrative and social imaginary marks a transcendental milestone in the art of postmodern symbols and codes captured in the semiospheres, a key aspect for the understanding and interpretation of social reality.